The Effect of Ultrasound Therapy and Muscle Energy Technique on a Case of a Young Adult with Thoracic Outlet Syndrome - Iman Santoso; Triana Karnadipa; Safitry Eka Putri (Proceedings, 2023)
Case description. This case study evaluates an adult male, 24 years old, diagnosed with thoracic outlet syndrome and referred to a physiotherapy clinic because of pain and stiffness in the forearm and an inability to lift a heavy object. A physiotherapy session was given twice a week for three weeks. In the first week, ultrasound and reciprocal inhibition were applied, in the second week ultrasound therapy and post-isometric relaxation were applied and in the last week, ultrasound therapy and a post-contraction stretch were applied. After five interventions, the combination of ultrasound therapy and muscle energy techniques improved the functional ability by about 86.97% (from 19.2 to 2.5) measured with the Disabilities of the Arm Shoulder and Hand questionnaire (DASH). This case study suggests that the combination of ultrasound therapy and muscle energy techniques used for thoracic outlet syndrome, including a home exercise plan with the continuous monitoring of posture correction, could allow the patient to return to work.